SDNOR, a Novel Antioxidative lncRNA, Is Essential for Maintaining the Normal State and Function of Porcine Follicular Granulosa Cells - Yangan Huo; Qiqi Li; Liu Yang; Xiaoxue Li; Chen Sun; Yang Liu; Honglin Liu; Zengxiang Pan; Qifa Li; Xing Du (MDPI AG, 2023)
Increasing evidence shows that lncRNAs, an important kind of endogenous regulator, are involved in the regulation of follicular development and female fertility, but the mechanism remain largely unknown. In this study, we found that SDNOR, a recently identified antiapoptotic lncRNA, is a potential multifunctional regulator in porcine follicular granulosa cells (GCs) through RNA-seq and multi-dimension analyses. SDNOR-mediated regulatory networks were established and identified that SOX9, a transcription factor inhibited by SDNOR, mediates SDNOR's regulation of the transcription of downstream targets. Functional analyses showed that loss of SDNOR significantly impairs GC morphology, inhibits cell proliferation and viability, reduces E2/P4 index, and suppresses the expression of crucial markers, including PCNA, Ki67, CDK2, CYP11A1, CYP19A1, and StAR. Additionally, after the detection of ROS, SOD, GSH-Px, and MDA, we found that SDNOR elevates the resistance of GCs to oxidative stress (OS) and also inhibits OS-induced apoptosis. Notably, GCs with high SDNOR levels are insensitive to oxidative stress, leading to lower apoptosis rates and higher environmental adaptability. In summary, our findings reveal the regulation of porcine GCs in response to oxidative stress from the perspective of lncRNA and demonstrate that SDNOR is an essential antioxidative lncRNA for maintaining the normal state and function of GCs.